Genetic Determinism vs. Phenotypic Plasticity in Protist Morphology. (28th March 2017) - Mulot, Matthieu; Marcisz, Katarzyna; Grandgirard, Lara; Lara, Enrique; Kosakyan, Anush; Robroek, Bjorn J. M.; Lamentowicz, Mariusz; Payne, Richard J.; Mitchell, Edward A. D.
Abstract: Untangling the relationships between morphology and phylogeny is key to building a reliable taxonomy, but is especially challenging for protists, where the existence of cryptic or pseudocryptic species makes finding relevant discriminant traits difficult. Here we use Hyalosphenia papilio (a testate amoeba) as a model species to investigate the contribution of phylogeny and phenotypic plasticity in its morphology. We study the response of H. papilio morphology (shape and pores number) to environmental variables in (i) a manipulative experiment with controlled conditions (water level), (ii) an observational study of a within‐site natural ecological gradient (water level), and (iii) an observational study across 37 European peatlands (climate). We showed that H. papilio morphology is correlated to environmental conditions (climate and water depth) as well as geography, while no relationship between morphology and phylogeny was brought to light. The relative contribution of genetic inheritance and phenotypic plasticity in shaping morphology varies depending on the taxonomic group and the trait under consideration. Thus, our data call for a reassessment of taxonomy based on morphology alone. This clearly calls for a substantial increase in taxonomic research on these globally still under‐studied organisms leading to a reassessment of estimates of global microbial eukaryotic diversity.